Separation of biologically relevant isomers on an Orbitrap mass spectrometer using high‐resolution drift tube ion mobility and varied drift gas mixtures. (10th April 2019) - Kaszycki, Julia L.; La Rotta, Aurelio; Colsch, Benoit; Fenaille, François; Dauly, Claire; Kamleh, Anas; Wu, Ching
Abstract : Rationale: Atmospheric pressure drift tube ion mobility is a powerful addition to the Orbitrap mass spectrometer enabling direct separation of isomers. Apart from offering high resolving power in a compact design, it also facilitates optimization of the separation gas, as shown here for a series of biologically relevant isomer pairs. Methods: An Excellims MA3100 High‐Resolution Atmospheric Pressure Ion Mobility Spectrometer (HR‐IMS) was coupled to a Thermo Scientific™ Q Exactive™ Focus hybrid quadrupole–Orbitrap™ mass spectrometer, using an Excellims Directspray™ Electrospray Ionization source and a gas mixture setup to provide various drift gases (air, CO2 and mixtures). This instrument combination was used to separate isomers of eight pairs of metabolites and gangliosides, optimizing drift gas conditions for best separation of each set. Results: All but one of the isomers pairs provided could be partially or fully separated by the HR‐IMS‐MS combination using ion mobility drift times. About half of the separated compounds showed significantly better analytical separation when analyzed in a mixture of CO2 and air rather than air or CO2 alone. Resolving power of up to 102 was achieved using the 10 cm atmospheric drift tube ion mobility add‐on for the Orbitrap mass spectrometer. Conclusions: The present analysis demonstrates the usefulness of using atmospheric drift tube IMS on an Orbitrap mass spectrometer to characterize the isomeric composition of samples. It also highlights the potential benefits of being able to quickly optimize the drift gas composition to selectively maximize the mobility difference for isomer separation.